Rare lymphatic malformation in an extreme premature infant: answer - Veronica Mugarab Samedi; Adel Elsharkawy (Hygeia Press di Corridori Marinella, 2017)
We present a case of massive cystic lymphangioma in an extreme preterm infant, which was initially diagnosed by prenatal ultrasound and confirmed by fetal MRI. Physical examination and postnatal ultrasound confirmed diagnosis of cystic lymphangioma. No other anomalies were detected, genetic screening for infant was normal. Despite of size of lymphatic malformation at birth, it was an isolated finding with minimal vascularity, thus the prognosis for self-resolution was very good. No surgical intervention was required other than skin care. The lesion started to decrease in size from day 5, and showed signs of gradual involution from the 2nd week of life. At 37 weeks of corrected gestational age lymphatic malformation underwent full resolution, with minimal pigmentation and scarring on the site of lesion.